1992
DOI: 10.1002/1097-0142(19920901)70:3+<1313::aid-cncr2820701518>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease and colon cancer

Abstract: Patients who have had extensive colitis for more than 10 years are at increased risk for colorectal cancer. The risk may be greatest for those whose onset of illness is in childhood. Management options for patients at increased risk include prophylactic colectomy or endoscopic surveillance. The object of surveillance is prevention of cancer by detecting premalignant lesions that predispose to cancer. A less desirable objective is the diagnosis of cancer at an early curable stage. Patients must be well informed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 22 publications
2
31
0
5
Order By: Relevance
“…[1][2][3] Recent studies suggest a cumulative incidence of carcinoma of about 5-10% at 20 years and 12-20% at 30 years from the onset of UC. 4) UC-associated neoplasia (UCAN) consists of dysplasia limited to the mucosal layer and invasive carcinomas. Dysplasia is subdivided into high-grade dysplasia (HGD), low-grade dysplasia (LGD), and indefinite dysplasia (IND) according to the histological grade.…”
supporting
confidence: 63%
“…[1][2][3] Recent studies suggest a cumulative incidence of carcinoma of about 5-10% at 20 years and 12-20% at 30 years from the onset of UC. 4) UC-associated neoplasia (UCAN) consists of dysplasia limited to the mucosal layer and invasive carcinomas. Dysplasia is subdivided into high-grade dysplasia (HGD), low-grade dysplasia (LGD), and indefinite dysplasia (IND) according to the histological grade.…”
supporting
confidence: 63%
“…We first fit a model (model 1) adjusted for age (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), and >60 years) only. For multivariable analyses (model 2), we additionally included sociodemographic factors, including gender, race-ethnicity (non-Hispanic white, non-Hispanic black, Mexican-American, other), level of education (less than high school, high school or more), annual family income (<$20,000, $20,000), and lifestyle-related variables, including body mass index (BMI; <25, 25-29.9, and 30 kg/m 2 ), pack-years of smoking, serum cotinine levels, alcohol consumption (g/day), and physical activity (more active, less active or about the same compared with others of same age).…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that IBD patients with proctitis and proctosigmoiditis are at the lowest risk of CACRC and the higher risk is combined with left-sided colitis and pan-colitis [15,16].…”
Section: Risk Factors In Cacrcmentioning
confidence: 99%